Crows on the Wire: intermediality in applied drama and conflict transformation – 'humanising' the police in Northern Ireland. Issue 3 (2nd July 2016) - Jennings, Matt
ABSTRACT: Crows on the Wire (COTW) is an intermedial project deploying applied theatre, educational drama and digital performance [Dixon, S. (2007). Digital Performance: A History of New Media in Theatre, Dance, Performance Art and Installation . Cambridge, MA: MIT Press] to explore the recent history of the peace process in Northern Ireland – specifically the 'transition' of the police force from the Royal Ulster Constabulary (RUC) to the Police Services Northern Ireland in November 2001. This 'rebranding' was a key element of the Good Friday Agreement (1998) that nominally ended the civil conflict known as 'The Troubles'. The COTW project, delivered by the Verbal Arts Centre based in Derry/Londonderry, expresses the anger and disaffection felt by some members of the RUC and the impact that this had on their sense of identity. It also addresses the perception that the RUC was sectarian and corrupt.